FIVE-YEAR OUTCOMES OF INTRAVITREAL INJECTION OF RANIBIZUMAB FOR THE TREATMENT OF MYOPIC CHOROIDAL NEOVASCULARIZATION. Issue 11 (November 2017) - Wu, Tsung-Tien; Kung, Ya-Hsin
Abstract : Purpose: To evaluate the 5-year outcomes, efficacy, and safety of intravitreal ranibizumab injections for the treatment of myopic choroidal neovascularization. Methods: The medical records of 18 consecutive eyes of 14 patients who received intravitreal injections of ranibizumab for myopic choroidal neovascularization with a follow-up of 5 years were retrospectively reviewed. Outcomes included best-corrected visual acuity, total number of treatments, and complications. Results: The average number of injections over 5 years was 4.56 ± 3.52. Ten eyes (55.56%) had no need for treatment after the first year. Mean best-corrected visual acuity improved from 0.59 ± 0.47 logarithm of the minimum angle of resolution (Snellen equivalent, 6/24) at baseline to 0.32 ± 0.35 logarithm of the minimum angle of resolution (Snellen equivalent, 6/13) at 1 year, and to 0.38 ± 0.42 logarithm of the minimum angle of resolution (Snellen equivalent, 6/15) at 2 years ( P = 0.001 and 0.020, respectively; paired t -test). After 2 years, although mean best-corrected visual acuity remained better than baseline, the difference was not statistically significant. At 5 years, vision improved by at least 1 line for 61.11% of eyes and by more than 3 lines for 33.33%. The final visual acuity of 2 eyes was worse than baseline because of disease activity and profound chorioretinal atrophy, which increased in six eyes. No complications were noted. Conclusion: Intravitreal ranibizumab was safe and effective for treating myopic choroidal neovascularization. Only 44% of eyes required retreatment after the first year, and vision improved in more than 60% of eyes over 5 years. Abstract : A retrospective study of intravitreal ranibizumab conducted revealed that it is a safe and effective treatment for myopic choroidal neovascularization. More than half the eyes treated had no need for treatment after the first year, and more than 60% had a visual gain over 5 years.